DETERMINASI KARAKTERISTIK PEKERJAAN, PERCEIVED ORGANIZATION SUPPORT, DAN KEADILAN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIO DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI - Sari, Marta Widian; Harahap, Erwin Hotmansyah; Sari, Vivi Nila (Jurnal ASET (Akuntansi Riset), 2019)
Abstract. This research was conducted at PT. Bank Mandiri (Persero), Tbk Especially in the Padang Micro Cluster. This study aims to find out how much influence Job Characteristics, Perceived Organization Support (POS), and Organizational Justice Against Organizational Citizenship Behavior (OCB) With Employee Engagement As a Mediation variable. The method in collecting research data through surveys and distributing questionnaires, with a sample of 96 Employee respondents. The analytical method used is multiple regression analysis. The results of the research obtained based on the partial test (t test) were obtained: (a) partially there was a significant effect between Job Characteristics on Employee Engagement. Thus Ho was rejected Ha accepted. (b) partially there is a significant influence between the Perceived Organization Support on Employee Engagement. Thus Ho is rejected Ha accepted. (c) partially there is a significant effect between Organizational Justice on Employee Engagement. Thus Ho is rejected Ha accepted. Finally the author suggested to PT. Bank Mandiri (Persero), Tbk. Especially in the Padang Micro Cluster, in order to further enhance Organizational Citizenship Behavior with Job Characteristics, Perceived Organization Support, Organizational Justice and Employee Engagement along with indicators of each variable.Keywords. employee engagement; job characteristics; organizational justice; organizational citizenship behavior; perceived organization support.Abstrak. Penelitian ini dilakukan pada PT. Bank Mandiri (Persero), Tbk Khususnya di Cluster Mikro Padang. Penelitian ini bertujuan untuk mengetahui seberapa besar Pengaruh Karakteristik Pekerjaan, Perceived Organization Support (POS), dan Keadilan Organisasi Terhadap Organizational Citizenship Behavior (OCB) Dengan Employee Engagement Sebagai variabel Mediasi. Metode dalam pengumpulan data penelitian melalui survey dan menyebarkan kuisioner, dengan sampel 96 responden Karyawan. Metode analisis yang digunakan adalah analisis regresi berganda. Hasil penelitian yang didapatkan berdasarkan uji parsial (uji t) diperoleh : (a) secara parsial terdapat pengaruh signifikan antara Karakteristik Pekerjaan Terhadap Employee Engagement. Dengan demikian Ho ditolak Ha diterima. (b) secara parsial terdapat pengaruh signifikan antara Perceived Organization Support terhadap Employee Engagement. Dengan demikian diperoleh Ho ditolak Ha diterima. (c) secara parsial terdapat pengaruh signifikan antara Keadilan Organisasi Terhadap Employee Engagement. Dengan demikian diperoleh Ho ditolak Ha diterima. Akhirnya penulis menyarankan kepada  PT. Bank Mandiri (Persero), Tbk Khususnya di Cluster Mikro Padang, agar dapat lebih meningkatkan Organizational Citizenship Behavior dengan Karakteristik Pekerjaan, Perceived Organization Support, Keadilan Organisasi dan Employee Engagement beserta indikator-indikator masing-masing variabel.Kata kunci. employee engagement; karakteristik pekerjaan; keadilan organisasi; organizational citizenship behavior; perceived organization support.